Carbon stocks on the intertidal seagrass meadow of the Indonesian Islands: Spatial and anthropogenic activities variability - Fery Kurniawan; Agustin Rustam; Robba Fahrisy Darus; Fauziyah; Almira Nadia Kusuma; Muhammad Noval Alghifari; Luky Adrianto; Yonvitner (Continental Shelf Research, 2026)

Spatio-temporal variation in progression rates of black band disease between Pramuka Island and Pari Island of the Seribu Islands, Indonesia - Ofri Johan Ofri; Rendy Ginanjar; Agustin Rustam; Idil Ardi; Lili Sholichah; Rita Rachmawati; Rikoh Manogar Siringoringo; Muhammad Abrar; Ni Wayan Purnama Sari; Giyanto; Andrias Steward Samusamu; Nani Ingrid Undap; et al. (Frontiers in Marine Science, 2024)
Black band disease (BBD) is one of the oldest recognized diseases of scleractinian corals. This disease is little known on the variation of progression rates across relatively small spatial scales and how local variations in the environment can impact prevalence and spread. The purpose of this study was to explore the progression of BBD on genus Montipora in relation to spatio-temporal environmental parameters in two islands of the Seribu Islands, North Jakarta, Indonesia during dry season and rainy season. Monthly underwater pictures were taken for determining the progress of disease level. Interestingly, the progression rate of the disease recorded at Pramuka Island was higher (8.10 cm 2 day -1 ) than the one at Pari Island (3.79 cm 2 day -1 ). In Pramuka Island, the infected corals had almost 89% of the dead surface, compared to only 68% at Pari Island. Similar to other studies in the region, we confirmed that the disease progressed faster during the dry season, where the environmental parameters, such as temperature, light intensity, and phosphate, were starting to increase, while total organic matter, current flow rates, and turbidity were lower. Progression of the disease was significantly different between seasons ( p <0.001), but not between sites ( p =0.118). Therefore, the progress of BBD has a higher impact at the more populated Pramuka island than at the less populated Pari Island, in addition to the influence of environmental parameters on coral vulnerability to diseases.

Sedimentary seagrass carbon stock and sources of organic carbon across contrasting seagrass meadows in Indonesia - Yusmiana P. Rahayu; Mariska A. Kusumaningtyas; August Daulat; Agustin Rustam; Devi D. Suryono; Hadiwijaya L. Salim; Restu N. A. Ati; Nasir Sudirman; Terry L. Kepel; Andreas A. Hutahaean; Novi S. Adi (Environmental Science and Pollution Research, 2023)
Seagrass meadows are an important component of coastal ecosystems globally, and they capture and store organic carbon in living biomass and sediments. Geographical estimates of blue carbon in seagrass habitats are regionally biased, with limited information from the Indo-Pacific region, including Indonesia. Seagrass extent in Indonesia is declining rapidly, and it has been suggested that marine protected areas (MPAs) are an important instrument to support protection of seagrass ecosystems and their services. Thus, this study is aimed at quantifying and comparing sedimentary carbon stocks and sources of organic carbon from seagrass meadows located in undisturbed areas outside MPA, disturbed areas outside MPA, and within MPA in three small islands in Indonesia. The sediment carbon stocks from this study ranged from 19.81 to 117.49 Mg C ha −1 , with the highest stock measured inside MPA (77.15 ± 1.38 Mg C ha −1 ), followed by undisturbed outside MPA (36.08 Mg C ha −1 ), and the lowest stock at disturbed outside MPA (21.86 ± 0.31 Mg C ha −1 ). The predominant source of organic carbon in disturbed meadows was from coastal POM (particulate organic matter, ~ 36%), while in MPA and undisturbed sites, the main source was from seagrass, with ~ 38% and ~ 60% contributions, respectively. The results of this study add more data and information on seagrass blue carbon potential from three different islands with different degrees of disturbance in Indonesia.

Assessing Carbon Stock and Sequestration of the Tropical Seagrass Meadows in Indonesia - A’an J. Wahyudi; Susi Rahmawati; Andri Irawan; Hadiyanto Hadiyanto; Bayu Prayudha; Muhammad Hafizt; Afdal Afdal; Novi S. Adi; Agustin Rustam; Udhi. E. Hernawan; Yusmiana P. Rahayu; Marindah Y. Iswari; et al. (Ocean Science Journal, 2020)